Rationale and design of a single-blind, randomised controlled trial of exercise training for managing learning and memory impairment in persons with multiple sclerosis. Issue 12 (14th December 2018) - Sandroff, Brian M; Motl, Robert W; Bamman, Marcus; Cutter, Gary R; Bolding, Mark; Rinker, John R; Wylie, Glenn R; Genova, Helen; DeLuca, John
Abstract : Introduction: This randomised controlled trial (RCT) examines treadmill walking exercise training effects on learning and memory performance, hippocampal volume, and hippocampal resting-state functional connectivity in persons with multiple sclerosis (MS) who have objective impairments in learning new information. Methods and analysis: Forty fully ambulatory persons with MS who demonstrate objective learning and memory impairments will be randomly assigned into either the intervention or active control study conditions. The intervention condition involves supervised, progressive treadmill walking exercise training three times per week for a 3-month period. The active control condition involves supervised, progressive low-intensity resistive exercise that will be delivered at the same frequency as the intervention condition. The primary outcome will involve composite performance on neuropsychological learning and memory tests, and the secondary outcomes involve MRI measures of hippocampal volume and resting-state functional connectivity administered before and after the 3-month study period. Outcomes will be administered by treatment-blinded assessors using alternate test forms to minimise practice effects, and MRI data processing will be performed by blinded data analysts. Ethics and dissemination: This study has been approved by a university institutional review board. The primary results will be disseminated via peer-reviewed publications and the final data will be made available to third parties in applicable data repositories. If successful, the results from this study will eventually inform subsequent RCTs for developing physical rehabilitation interventions (ie, treadmill walking exercise training) for improving learning and memory and its relationship with hippocampal outcomes in larger samples of cognitively impaired persons with MS. The results from this early-phase RCT will further lay preliminary groundwork for ultimately providing clinicians and patients with guidelines for better using chronic treadmill walking exercise for improving cognition and brain health. This approach is paramount as learning and memory impairment is common, burdensome and poorly managed in MS. Trial registration number: NCT03319771 ; Pre-results.